Inclusive leadership can improve nurses’ psychological ownership and reduce their turnover intention under the normalization of COVID-19 prevention - Zeng, Dongyu; Wang, Baoxiang; Chen, Weiju (Frontiers in Psychology, 2023)
Introduction The COVID-19 pandemic continues to impact people’s lives and professions worldwide. Chinese nurses face immense work pressure under the normalization of COVID-19 prevention and control, resulting in greater turnover intention. It is, therefore, crucial to study the mechanisms that influence the turnover intention of nurses in this situation. Objective Many studies have examined the impact of leadership style on nurses’ turnover intention; however, few researchers have investigated this influence during the COVID-19 pandemic. Based on the leader-member exchange theory, this study empirically studied the effect of inclusive leadership on turnover intention of nurses under the normalization of COVID-19 prevention and control in China, while assessing the mediating role of psychological ownership. Design Cross-sectional study with multi-center data. Participants Two thousand, two hundred ninety-nine registered nurses from 17 hospitals in China were recruited from January to March, 2022, under the normalization of COVID-19 prevention and control in China. Methods A demographic questionnaire and scales of inclusive leadership, psychological ownership, and turnover intention integrated into an online survey were sent to registered nurses of different hospitals. Maximum likelihood structural equation modeling (ML-SEM) was used to analyze data. Results Independent variable inclusive leadership has a significant effect on the overall turnover intention of nurses, p < 0.001. The direct effect path coefficient from inclusive leadership to psychological ownership is significant, p < 0.001. The direct effect path coefficient from psychological ownership to turnover intention is significant, p < 0.001. The indirect effect path coefficient from inclusive leadership to turnover intention is significant, p < 0.001. Conclusion Psychological anxiety, burnout, turnover intention, and even suicidal thoughts were the main symptoms of Chinese nurses under the normalization of COVID-19 prevention and control in China. The absence of a mechanism to counteract these negative conditions may ultimately lead to personal psychological distress for nurses and collapse of the healthcare system. Inclusive leadership can improve nurses’ psychological ownership level and reduce their turnover intention by treating them fairly, providing them with opportunities for self-development, paying attention to communication with them, and increasing their sense of belonging, self-efficacy, and self-identity.